2019
DOI: 10.32894/kujss.2019.14.3.2
|View full text |Cite
|
Sign up to set email alerts
|

DNA Sequences of qacE∆1 Gene in Pseudomonas Aeruginosa Isolated from Wounds and Burns Infections.

Abstract: A total of 69 isolates of Pseudomonas aeruginosa were obtained from different clinical samples including wounds 24 (35%) and burns 67 (65%)، the genes that responsible for Pseudomonas aeruginosa resistance isolates was detected, the results showed that quaternary ammonium compound delta 1 (qacE∆1) gene was 97.1% in Pseudomonas aeruginosa isolation. 24 (35%) in the wounds and 63 (62.31%) in burns, the size of the gene showed 285 bp, the results of the qacE∆1 analysis showed a single mutation of the mutation typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…Conversely, the IMVIC test suite, encompassing Indole production, Methyl Red (MR), Vocus-Proscar (VP), and Citrate utilization examinations, yielded predominantly negative results, except for the Citrate utilization test which yielded affirmative results. Notably, these findings concur with investigations conducted within Iraq (13) The current investigation documented the percentage of resistance displayed by P. aeruginosa bacteria towards Fluoroquinolones, a class of antibiotics renowned for their efficacy against this bacterial strain. The results indicated the highest resistance of Levofloxacin (LEV) and Ciprofloxacin (CIP) (38% and 22%, respectively).…”
Section: Discussionsupporting
confidence: 89%
“…Conversely, the IMVIC test suite, encompassing Indole production, Methyl Red (MR), Vocus-Proscar (VP), and Citrate utilization examinations, yielded predominantly negative results, except for the Citrate utilization test which yielded affirmative results. Notably, these findings concur with investigations conducted within Iraq (13) The current investigation documented the percentage of resistance displayed by P. aeruginosa bacteria towards Fluoroquinolones, a class of antibiotics renowned for their efficacy against this bacterial strain. The results indicated the highest resistance of Levofloxacin (LEV) and Ciprofloxacin (CIP) (38% and 22%, respectively).…”
Section: Discussionsupporting
confidence: 89%
“…The polymerase chain reaction used for the detection of 25 DNA samples of carbapenem resistance P. aeruginosa isolates, the results of the reaction and gel electrophoresis revealed the alg D gene percentage was 100% with bands appearing within the estimated size of the gene (1310 bp.) that showed in the Figure (4). This result is consistent with Ellappan et al 2018 who indicated that alg D was 93% of carbapenem resistance isolates they indicated that the coexistence of different antimicrobial resistance mechanisms together with virulence genes in carbapenem-resistant isolates has become an alarming increasing threat, constantly monitoring of multidrug-resistant pathogens is critical for clinicians to identify treatment options against such infections (Ellappan et al, 2018).…”
Section: Resultssupporting
confidence: 82%
“…The situation differed for the qacE gene, which was reported differently from prior Iranian studies (1.1% to 26.3%) (Table 3). The documented rate of the qacE∆1 gene was lower in Germany (10%) (22) when its reported rate was higher in other countries (Table 3) (39,(44)(45)(46)(47)(48)(49). The qacE gene frequency was lower among P. aeruginosa isolates from Germany (2.7%) (22), but several other studies reported a higher rate of qacE genes (33% -100%) (39,44,46,48,49) (Table 3).…”
Section: Discussionmentioning
confidence: 91%